A Requirement Model Of Local News WEB/WAP Application For Rural Communities - Al-msie'deen, Ra'fat Ahmad Ali (2008)
Mobile news service for can be obtained easily way and flexibility to access the rural news criteria at any time in any location that this service can provide. This research introduces a prototype "local news WAP/WEB application" that provides the people in the rural communities with the appropriate news services that could help those people to view the various news via this prototype. By using this prototype, the user of this service from the rural communities can easily get necessary information that makes those users in touch with the different news updating in these areas. The proposed prototype provide the user to post the occur news that related for these areas.